2021
DOI: 10.7759/cureus.20208
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Empagliflozin With Vitamin D Supplementation in Peripheral Neuropathy in Type 2 Diabetic Patients

Abstract: Background: Neuropathy is the most prevalent broad-spectrum microvascular complication of diabetes. The present study aims to evaluate the effect of empagliflozin with vitamin D supplementation on diabetic peripheral neuropathy.Methods: A prospective, randomized, controlled study was conducted for six months including 150 type 2 diabetic patients, divided into three groups (n=50/group): Group 1, patients on oral hypoglycemic agents; Group 2, patients on empagliflozin and Group 3, patients on empagliflozin with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…In the study of the effect of empagliflozin on diabetic microvascular complications, Eid et al (32) did not find any effect on neuropathy in T2DM subjects. In the study of Mehta et al (33) patients using empagliflozin did not detect any difference in the improvement of diabetic neuropathy when compared to patients using other oral antihyperglycemic drugs. In our study, we did not find any changes in the biochemical and hemogram parameters of diabetic neuropathy patients using empagliflozin in accordance with the literature.…”
Section: Discussionmentioning
confidence: 87%
“…In the study of the effect of empagliflozin on diabetic microvascular complications, Eid et al (32) did not find any effect on neuropathy in T2DM subjects. In the study of Mehta et al (33) patients using empagliflozin did not detect any difference in the improvement of diabetic neuropathy when compared to patients using other oral antihyperglycemic drugs. In our study, we did not find any changes in the biochemical and hemogram parameters of diabetic neuropathy patients using empagliflozin in accordance with the literature.…”
Section: Discussionmentioning
confidence: 87%
“…Based on the Cochrane Collaboration’s tool for assessing the risk of bias, all four included RCTs ( Jordan et al, 2017 ; Shimizu et al, 2020 ; Mehta et al, 2021 ; Liao et al, 2022 ) showed a low risk of selection bias, performance bias, and reporting bias. Three studies ( Jordan et al, 2017 ; Mehta et al, 2021 ; Liao et al, 2022 ) showed an unclear risk of selection bias, while two ( Jordan et al, 2017 ; Mehta et al, 2021 ) showed a high risk of detection bias. Three of the four studies ( Shimizu et al, 2020 ; Mehta et al, 2021 ; Liao et al, 2022 ) showed a low risk of attribution bias, and one study ( Jordan et al, 2017 ) showed a high risk.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (Jordan et al, 2017;Mehta et al, 2021;Liao et al, 2022) showed an unclear risk of selection bias, while two (Jordan et al, 2017;Mehta et al, 2021) showed a high risk of detection bias. Three of the four studies (Shimizu et al, 2020;Mehta et al, 2021;Liao et al, 2022) showed a low risk of attribution bias, and one study (Jordan et al, 2017) showed a high risk. The NIH quality assessment tool revealed that two studies (Wang et al, 2019;Sardu et al, 2022) were good quality (Figure 2 and Table 1).…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 98%
“…En cuanto a la información sobre el rol de la vitamina D en pacientes con diabetes mellitus tipo 2 (Tabla 1), la mayoría de artículos se relacionaba con la diabetes mellitus tipo 2, pero también hacía más relación a los otros diferentes tipos de diabetes como la diabetes tipo 1 o sus complicaciones como neuropatía diabética, pie diabético o relacionadas al sistema cardiovascular. (11,13,14,16,17,19,23,24,25,26,27) Las características fundamentales del diseño y resultados de los estudios sobre el rol de la vitamina D en pacientes diabéticos tipo II se muestra en la Tabla 2.…”
Section: Resultados Y Discusiónunclassified